Phonon dispersion of buckled two-dimensional GaN - Zhenyu Zhang; Tao Wang; Hailing Jiang; Xifan Xu; Jinlin Wang; Ziruo Wang; Fang Liu; Ye Yu; Yuantao Zhang; Ping Wang; Peng Gao; Bo Shen; et al. (Nature Communications)
Abstract Group-III nitride semiconductors such as GaN have various important applications based on their three-dimensional form. Previous work has demonstrated the realization of buckled two-dimensional GaN, which can be used in GaN-based nanodevices. However, the understanding of buckled two-dimensional GaN remains limited due to the difficulties in experimental characterization. Here, for the first time, we have experimentally determined the phonon dispersion of buckled two-dimensional GaN by using monochromatic electron energy loss spectroscopy in conjunction with scanning transmission electron microscopy. A phonon band gap of ~40 meV between the acoustic and optical phonon branches is identified for buckled two-dimensional GaN. This phonon band gap is significantly larger than that of ~20 meV for the tetrahedral-coordinated three-dimensional GaN. Our theoretical calculations confirm this larger phonon band gap. Our findings provide critical insights into the phonon behavior of buckled two-dimensional GaN, which can be used to guide high-performance thermal management in GaN-based high-power devices.